THE IMPLEMENTATION OF THE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) COOPERATIVE LEARNING MODEL IN IMPROVING STUDENTS’ LEARNING OUTCOMES ON SMALL BALL GAME MATERIALS FOR YEAR VII-A STUDENTS OF MTSN 3 WEST ACEH IN 2020-2021 ACADEMIC YEAR - Badrussalim Badrussalim; Riki Irawan (FKIP Universitas Al Washliyah Medan, 2021)
This study aims